1994
DOI: 10.1063/1.467664
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical study of lithium–C60 clusters

Abstract: Semiempirical quantum chemical calculations at the modified-neglect-of-diatomic-overlap self-consistent-field level are performed for differently charged clusters of composition LixC60 with x=0...14. The ground state energies of various isomers are calculated to find the most stable configuration for each cluster stoichiometry. The energies required to remove a Li-atom from these configurations are calculated to determine abundance spectra of distributions of heated LixC60 clusters. These spectra show intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…30,31 For alkaline earth materials it is now commonly accepted that many atoms homogeneously surround the C 60 molecule in spherically centred shells. For other metals, such as lithium 5,11,12,21 a strong charge transfer takes place with carbon and the resulting ionic interaction may be stronger than the metallic bonding. As a consequence, homogeneous coating of C 60 is also observed at low coverage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 For alkaline earth materials it is now commonly accepted that many atoms homogeneously surround the C 60 molecule in spherically centred shells. For other metals, such as lithium 5,11,12,21 a strong charge transfer takes place with carbon and the resulting ionic interaction may be stronger than the metallic bonding. As a consequence, homogeneous coating of C 60 is also observed at low coverage.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28][29] Coverage of fullerenes with semiconductor atoms or clusters has also been investigated. 30,31 For alkaline earth materials it is now commonly accepted that many atoms homogeneously surround the C 60 molecule in spherically centred shells.…”
Section: Introductionmentioning
confidence: 99%
“…The deviations from the icosahedral shape correspond to symmetry breakings which may induce important modifications in the energy sequence and degeneracies of the one-electron levels, thereby affecting the optical properties. On the other hand, metallic screening is also expected to become increasingly important, due to the mobile valence electrons of the metal coating atoms, which will fill the weakly bound states of the cluster.The symmetry breaking effect has been conjectured [3] in order to interpret the abundance spectra of alkalicoated fullerenes, and corroborated by the results of the simulations carried out by Martin's group [4]. In this context, Li C is a very special cluster, since it is the only cluster predicted so far to maintain the symmetry of the fullerene seed.…”
mentioning
confidence: 76%
“…The lithium coating experiments confirmed the special stability of the Li C cluster, which develops also a well defined peak in the mass spectra of singly and doubly ionized lithium-coated C clusters. Theoretically, a good deal is known about the structural properties of Li C [2], as well as other lithiumcoated fullerenes [4]. This is not the case concerning their optical properties, which are expected to display a sizedependent behaviour.…”
Section: Introductionmentioning
confidence: 97%
“…The stability of this system was also confirmed by MNDO calculations. 17 In addition, the calculations of C60Li ~ complexes (for n varied from I to 14) 17 showed that at n < 9 the Li atoms are coordinated preferably to hexagonal faces, whereas at n > 9 coordination to pentagonal faces occurs.…”
Section: The Third Possible Procedures Of Stabilization Of C60mentioning
confidence: 98%